A double-triangle-hole splayed small-molecule single crystal material, a preparation method and applications thereof
Patent Information
- Application Number
- CN202611127893.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]然而,现有研究主要集中于碘蒸气或固相碘吸附,针对饱和碘水溶液中碘的吸附报道较少
本发明采用醛类单体和胺类单体作为主要原料,通过席夫碱缩合反应获得目标小分子单晶材料,合成路线清晰,结构可设计性强。
Smart Images

Figure REF-OBJ-1785221143929-000001 
Figure REF-OBJ-1785221143929-000003 
Figure REF-OBJ-1785221143929-000004
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials chemistry technology, specifically relating to a double-triangular-pore figure-eight shaped small molecule single crystal material, its preparation method, and its application. Background Technology
[0002] Iodine and its isotopes are widely found in nuclear energy, medicine, chemical industry, and environmental remediation. Radioactive iodine, in particular, has strong environmental mobility and bioaccumulation risks. Once inside the human body, it easily accumulates in the thyroid gland, causing internal radiation damage and increasing the risk of thyroid injury and related diseases. Therefore, developing adsorbent materials capable of efficiently capturing iodine is of great significance for the treatment of iodine-containing wastewater, the control of radioactive iodine pollution, and environmental safety protection.
[0003] Currently, materials used for iodine adsorption mainly include activated carbon, silver-based adsorbents, metal-organic frameworks (MOFs), covalent organic frameworks (COFs), porous organic polymers, and porous organic cages. These materials generally capture iodine molecules through pore confinement, halogen bonding, charge transfer, coordination, and host-guest interactions. Although significant progress has been made in related research, some challenges remain in the remediation of aqueous iodine pollution. For example, while silver-based materials have good adsorption performance, they are costly and involve issues such as metal resource consumption and subsequent treatment. Meanwhile, metal and covalent organic framework materials have complex preparation processes, high costs, and their ability to capture iodine in aqueous solutions needs improvement.
[0004] During the adsorption of iodine in a saturated aqueous solution, the presence of iodine in water is complex and may involve I₂ and I₂. 3- And polyiodine anions. Therefore, small-molecule single-crystal materials with well-defined structural characteristics and the advantage of elucidated host-guest interactions have become important systems for studying iodine adsorption behavior. Small-molecule single-crystal materials have advantages such as well-defined structures, designable compositions, and clear crystal stacking methods, and have application potential in the field of iodine adsorption. Compared with traditional porous materials, they achieve selective recognition and enrichment of iodine molecules through the regulation of molecular structure and functional groups.
[0005] However, existing research mainly focuses on iodine vapor or solid-phase iodine adsorption, with few reports on iodine adsorption in saturated iodine aqueous solutions. Therefore, developing a small-molecule single-crystal adsorbent suitable for iodine-saturated aqueous solutions, capable of adsorbing iodine under aqueous conditions while maintaining good stability, has significant research value and application prospects. Summary of the Invention
[0006] The present invention aims to provide a small-molecule single-crystal material for iodine adsorption in iodine-saturated aqueous solutions, its preparation method, and its application. This small-molecule single-crystal material is formed by the Schiff base condensation reaction of an ortho-dialdehyde monomer and a tetraamine monomer. It possesses a well-defined molecular structure and crystal packing mode, containing aromatic rings, nitrogen atoms, oxygen atoms, and other structural units. It can capture iodine molecules in the aqueous phase through aromatic π-electron interactions, host-guest interactions, and charge transfer.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a double triangular hole figure-eight shaped small molecule single crystal material, wherein the single crystal material is prepared by a Schiff base condensation reaction of an aldehyde monomer represented by any one of the following formulas (I) or (II) and an amine monomer represented by any one of the following formulas (III), (IV) or (V). Among them, the single crystal material obtained by the aldehyde monomer shown in formula (I) or formula (II) and the amine monomer shown in formula (V) is prepared by Schiff base condensation reaction and protonation of nitrogen-containing sites by protonating reagent; .
[0008] Furthermore, in the single crystal material of the present invention, the single crystal material is prepared by Schiff base condensation reaction of aldehyde monomers shown in formula (I) or formula (II) and amine monomers shown in formula (III). Preferably, the single crystal material is prepared by Schiff base condensation reaction of the aldehyde monomer of formula (I) and the amine monomer of formula (III).
[0009] Furthermore, in the single crystal material of the present invention, the single crystal material is prepared by Schiff base condensation reaction of aldehyde monomers shown in formula (I) or formula (II) and amine monomers shown in formula (IV). Preferably, the single crystal material is prepared by Schiff base condensation reaction of the aldehyde monomer of formula (II) and the amine monomer of formula (IV).
[0010] Furthermore, in the single crystal material of the present invention, the single crystal material is prepared by Schiff base condensation reaction of aldehyde monomers shown in formula (I) or formula (II) and amine monomers shown in formula (V), and then protonating the nitrogen-containing sites with a protonating reagent. Preferably, the single crystal material is prepared by Schiff base condensation reaction of the aldehyde monomer of formula (I) and the amine monomer of formula (V), and then by protonation of the nitrogen-containing sites with a protonating agent.
[0011] Furthermore, in the single-crystal material described in this invention, the protonating agent is trifluoroacetic acid.
[0012] Furthermore, in the single-crystal material of the present invention, the aldehyde monomer of formula (I) is prepared by reacting salicylic acid and 1,4-dibromobutane; the aldehyde monomer of formula (II) is prepared by reacting salicylic acid and 1,6-dibromohexane.
[0013] Secondly, the present invention provides a method for preparing the single-crystal material described herein, comprising the following steps: (1) The aldehyde monomer and amine monomer are dissolved in an organic solvent and subjected to Schiff base condensation reaction under the conditions of catalyst and regulator to obtain an organic host containing an imine bond; (2) The reaction system containing the organic host is subjected to static reaction and crystal culture to obtain single crystal material; or the nitrogen-containing sites in the organic host are protonated in the presence of a protonating agent and crystal culture is carried out to obtain single crystal material.
[0014] Furthermore, in the preparation method of the present invention, in the process of preparing single crystal materials by using aldehyde monomers of formula (I) or formula (II) and amine monomers of formula (III) or formula (IV), the catalyst is pure acetic acid and the regulator is aniline.
[0015] Furthermore, in the preparation method of the present invention, during the preparation of single crystal materials from aldehyde monomers of formula (I) or formula (II) and amine monomers of formula (V), the catalyst is trifluoroacetic acid and the regulator is trifluoroethylamine.
[0016] Thirdly, the present invention provides an application of the single crystal material described above or the single crystal material prepared by the preparation method described above in the preparation of iodine adsorbent materials.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention uses aldehyde monomers and amine monomers as the main raw materials to obtain the target small molecule single crystal material through Schiff base condensation reaction. The synthesis route is clear and the structure is highly designable.
[0018] The small molecule single crystal material obtained by this invention has a clear single crystal structure, mild preparation conditions, and its molecular configuration and crystal stacking mode can be determined by single crystal X-ray diffraction, which is beneficial for analyzing iodine adsorption sites and adsorption mechanisms at the molecular level.
[0019] The small-molecule single-crystal material obtained in this invention contains structural units such as aromatic rings, imine bonds, nitrogen atoms, and oxygen atoms. It can interact with iodine molecules through π-I² interactions, halogen bonding, charge transfer, or host-guest interactions, thereby capturing iodine from iodine-saturated aqueous solutions. In adsorption tests on iodine-saturated solutions, the highest adsorption capacity reached 2973.42 mg / g, achieving excellent iodine adsorption performance. Therefore, the small-molecule single-crystal material prepared in this invention has promising application prospects in iodine adsorption. Attached Figure Description
[0020] Figure 1 The image shows the single-crystal X-ray diffraction structure of the small molecule single-crystal material M1 prepared in Example 1 of this invention.
[0021] Figure 2 The image shows the single-crystal X-ray diffraction structure of the small molecule single-crystal material M2 prepared in Example 2 of this invention.
[0022] Figure 3 The image shows the single-crystal X-ray diffraction structure of the small molecule single-crystal material M3 prepared in Example 3 of this invention.
[0023] Figure 4 The images show the UV-Vis absorption spectra of iodine aqueous solutions of different concentrations.
[0024] Figure 5 This is a standard curve of UV-Vis absorption for an aqueous solution of iodine saturated with water.
[0025] Figure 6 The images show the changes in the UV-Vis absorption spectra of iodine aqueous solution during the iodine adsorption process of the single-crystal materials M1, M2, and M3 of this invention. (a) shows the changes in the UV-Vis absorption spectra of iodine aqueous solution during the iodine adsorption process of single-crystal material M1; (b) shows the changes in the UV-Vis absorption spectra of iodine aqueous solution during the iodine adsorption process of single-crystal material M2; and (c) shows the changes in the UV-Vis absorption spectra of iodine aqueous solution during the iodine adsorption process of single-crystal material M3.
[0026] Figure 7 The diagram shows the iodine adsorption kinetics curves of the single crystal materials M1, M2 and M3 of this invention.
[0027] Figure 8 shows a comparison of powder X-ray diffraction before and after iodine adsorption in the small molecule single crystal material M3 of the present invention. Detailed Implementation
[0028] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application are described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of this application. However, this application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of this application. Unless otherwise specified, the materials, reagents, etc., used in the following embodiments are commercially available.
[0030] The present application is described in detail below with reference to specific embodiments, which are used for understanding and not for limiting the present application.
[0031] In a first aspect, the present invention provides a double triangular hole figure-eight shaped small molecule single crystal material, wherein the single crystal material is prepared by a Schiff base condensation reaction of an aldehyde monomer represented by formula (I) or formula (II) of the present invention and an amine monomer represented by any one of formula (III), formula (IV) or formula (V). The single-crystal material obtained by the aldehyde monomer shown in formula (I) or formula (II) and the amine monomer shown in formula (V) is prepared by Schiff base condensation reaction and protonation of nitrogen-containing sites by protonating reagent.
[0032] In some embodiments, the single crystal material is prepared by Schiff base condensation reaction of an aldehyde monomer of formula (I) or formula (II) with an amine monomer of formula (III); Preferably, in some embodiments, the single crystal material is prepared by Schiff base condensation reaction of the aldehyde monomer of formula (I) and the amine monomer of formula (III).
[0033] In some embodiments, the single crystal material is prepared by Schiff base condensation reaction of an aldehyde monomer of formula (I) or formula (II) with an amine monomer of formula (IV); Preferably, in some embodiments, the single crystal material is prepared by Schiff base condensation reaction of the aldehyde monomer of formula (II) and the amine monomer of formula (IV).
[0034] In some embodiments, the single crystal material is prepared by Schiff base condensation reaction of an aldehyde monomer of formula (I) or formula (II) and an amine monomer of formula (V), followed by protonation of the nitrogen-containing sites by a protonating agent. Preferably, in some embodiments, the single crystal material is prepared by Schiff base condensation reaction of the aldehyde monomer of formula (I) and the amine monomer of formula (V), and then by protonation of the nitrogen-containing sites with a protonating agent.
[0035] Furthermore, in the single-crystal material described in this invention, the protonating agent is trifluoroacetic acid.
[0036] Furthermore, in the single-crystal material of the present invention, the aldehyde monomer of formula (I) is prepared by reacting salicylic acid and 1,4-dibromobutane; the aldehyde monomer of formula (II) is prepared by reacting salicylic acid and 1,6-dibromohexane.
[0037] Secondly, the present invention provides a method for preparing the single-crystal material described herein, comprising the following steps: (1) The aldehyde monomer and amine monomer are dissolved in an organic solvent and subjected to Schiff base condensation reaction under the conditions of catalyst and regulator to obtain an organic host containing an imine bond; (2) The reaction system containing the organic host is subjected to static reaction and crystal culture to obtain single crystal material; or the nitrogen-containing sites in the organic host are protonated in the presence of a protonating agent and crystal culture is carried out to obtain single crystal material.
[0038] Furthermore, in the preparation method of the present invention, in the process of preparing single crystal materials by using aldehyde monomers of formula (I) or formula (II) and amine monomers of formula (III) or formula (IV), the catalyst is pure acetic acid and the regulator is aniline.
[0039] Furthermore, in the preparation method of the present invention, during the preparation of single crystal materials from aldehyde monomers of formula (I) or formula (II) and amine monomers of formula (V), the catalyst is trifluoroacetic acid and the regulator is trifluoroethylamine.
[0040] Thirdly, the present invention provides an application of the single crystal material described above or the single crystal material prepared by the preparation method described above in the preparation of iodine adsorbent materials.
[0041] The aldehyde monomers used in this invention are dialdehyde compounds with two ortho-aldehyde groups. First, dialdehyde monomers with different flexible chain lengths were synthesized, and their preparation method is as follows: they were obtained by etherification reaction of salicylaldehyde with dibromoalkanes of different chain lengths. By changing the length of the connecting carbon chain, the flexibility and spatial configuration of the obtained dialdehyde monomers can be adjusted, thereby further affecting the molecular packing mode and crystal structure of the subsequent Schiff base condensation products.
[0042] 1. The specific preparation steps for the dialdehyde monomer (named A1) based on 1,4-dibromobutane are as follows: (1) Add 7.325 g of salicylaldehyde and 5.8 g of 1,4-dibromobutane to a reaction vessel, add 14.5 g of potassium carbonate, and then add N,N-dimethylformamide as a reaction solvent. The reaction system was placed in an oil bath at 110 °C and stirred for 18 h under argon protection. (2) After the reaction was complete, the reaction system was cooled to room temperature and deionized water was added. The product precipitated from the system. It was then filtered, washed, and dried. The resulting solid was dried to obtain the crude ortho-dialdehyde product. (3) The crude product was dissolved in chloroform, and then diethyl ether was added to the solution to precipitate the ortho-dialdehyde monomer. After filtration, washing and drying, the purified ortho-dialdehyde monomer of the present invention with structural formula (I) was obtained.
[0043] 2. The specific preparation steps for the dialdehyde monomer (A2) based on 1,6-dibromohexane are as follows: (1) Add 7.325 g of salicylaldehyde and 6.7 g of 1,6-dibromohexane to a reaction vessel, add 14.5 g of potassium carbonate, and then add N,N-dimethylformamide as a reaction solvent. The reaction system was placed in an oil bath at 110 °C and stirred for 18 h under argon protection. (2) After the reaction was complete, the reaction system was cooled to room temperature and deionized water was added. The product precipitated from the system. It was then filtered, washed, and dried. The resulting solid was dried to obtain the crude ortho-dialdehyde product. (3) The crude product was dissolved in chloroform, and then diethyl ether was added to the solution to precipitate the ortho-dialdehyde monomer. After filtration, washing and drying, the purified ortho-dialdehyde monomer of the present invention with structural formula (II) was obtained.
[0044] By reacting the two dialdehyde monomers with different amine monomers through Schiff base condensation reactions, organic small molecule single crystal materials with different crystal structures and iodine adsorption properties can be obtained, as detailed in the following examples.
[0045] Example 1: Preparation of single-crystal material M1 8.1 mg of dialdehyde monomer A1 and 6.6 mg of amine monomer (compound of structural formula III described in this invention) were dissolved separately in 0.5 mL of tetrahydrofuran organic solvent. Then, 100 μL of acetic acid as a catalyst and 50 μL of aniline as a regulator were added to the above solutions, and the two solutions were mixed thoroughly. The mixed reaction solution was filtered through a 0.22 μm organic filter membrane to remove undissolved impurities. The filtered clear solution was placed in a sealed glass bottle and incubated at 60 °C for 2 days. After incubation, a yellow rod-shaped single crystal material M1 was obtained.
[0046] Single-crystal X-ray diffraction (SCD) was performed on the single crystal obtained in this embodiment, which exhibited complete morphology, good transparency, and suitable size. The results showed that the obtained material is a small-molecule single-crystal material with a well-defined molecular structure. The molecular formula of the obtained single-crystal material, determined by single-crystal X-ray diffraction, is C2. 66 H 54 N4O4 belongs to the triclinic crystal system and has a space group of P-1.
[0047] Example 2 Preparation of single crystal material M2 9.8 mg of dialdehyde monomer A2 and 7.1 mg of tetraamine monomer (compound of structural formula IV described in this invention) were weighed and dissolved separately in 0.5 mL of tetrahydrofuran organic solvent. Then, 100 μL of acetic acid as a catalyst and 50 μL of aniline as a regulator were added to the above solutions, and the two solutions were mixed thoroughly. The mixed reaction solution was filtered through a 0.22 μm organic filter membrane to remove undissolved impurities. The filtered transparent solution was placed in a sealed glass bottle and incubated at 60 °C for 2 days. After incubation, yellow rod-shaped single crystal material M2 was obtained.
[0048] Single-crystal X-ray diffraction (XRD) tests were conducted on the single crystal obtained in this embodiment, which exhibited complete morphology, good transparency, and suitable size. The test results indicate that the obtained material is a small-molecule single-crystal material with a well-defined molecular structure. The single-crystal XRD results also show that the molecular formula of the obtained material M2 is C2. 70 H 64 N6O4 belongs to the triclinic crystal system and has a space group of P-1.
[0049] Example 3: Preparation of protonated single-crystal material M3 8.9 mg of dialdehyde monomer A1 and 6.6 mg of amine monomer (compound of structural formula V described in this invention) were dissolved in tetrahydrofuran until fully dissolved. Then, 100 μL of trifluoroacetic acid and 50 μL of trifluoroethylamine were added to the reaction system. The reaction was carried out under acidic conditions at 60 °C for 2 days to induce Schiff base condensation, forming an organic host containing imine bonds. The protonated organic host and trifluoroacetate groups self-assembled through electrostatic interactions, hydrogen bonding, and intermolecular interactions, resulting in a protonated single-crystal material M3 through slow crystallization. The protonation sites of M3 occurred at the nitrogen-containing positions of the four imine bonds. X-ray diffraction results of M3 showed that two nitrogen-containing positions were protonated. Theoretically, increasing the amount of trifluoroacetic acid can increase the number of protonated sites.
[0050] Single-crystal X-ray diffraction (XRD) tests were conducted on the single crystals obtained in this embodiment, which exhibited complete morphology, good transparency, and suitable size. The test results indicate that the obtained material is a small-molecule single-crystal material with a well-defined molecular structure.
[0051] Single-crystal X-ray diffraction analysis of the obtained material showed that M3 is composed of a protonated organic host and trifluoroacetate, and its total molecular formula is C3. 66 H 54 F6N4O8 is a crystal containing a protonated organic host and two trifluoroacetate ions; it has a triclinic crystal system and a space group of P-1.
[0052] Example 4
[0053] The preparation process of Example 4 is basically the same as that of Example 1, except that the dialdehyde monomer is A2. The obtained product is named M4.
[0054] Example 5
[0055] The preparation process of Example 5 is basically the same as that of Example 1, except that the dialdehyde monomer is A1. The obtained product is named M5.
[0056] Example 6
[0057] The preparation process of Example 6 is basically the same as that of Example 1, except that the dialdehyde monomer is A2. The obtained product is named M6.
[0058] Based on the preparation results, the preparation processes of Examples 4-6 did not yield ideal single-crystal structure materials.
[0059] The following are the performance tests conducted on the single-crystal materials prepared in steps 1-3.
[0060] 1. Single crystal structure characterization Single-crystal materials M1, M2, and M3 prepared in Examples 1-3 were subjected to single-crystal X-ray diffraction tests. The obtained crystal structures are shown below. Figure 1-3 As shown, the relevant crystallographic parameters are summarized in Table 1. Single-crystal X-ray diffraction results show that the samples obtained in Examples 1-3 can all obtain resolvable single-crystal structures, and the molecular configurations and crystal packing methods of M1, M2 and M3 can be determined accordingly.
[0061] Table 1. Main crystallographic data of single crystal materials M1, M2 and M3
[0062] 2. Iodine adsorption performance testing of different organic small molecule single crystal materials First, a standard curve for the ultraviolet-visible absorption of iodine aqueous solution was established.
[0063] Figure 4 shows the quantitative calculation of the adsorption capacity of small molecule single crystal materials for iodine in iodine-saturated aqueous solution. Iodine-saturated aqueous solution was used as the mother liquor, and iodine standard solutions of different concentrations were prepared by stepwise dilution. The absorbance of each standard solution at the characteristic absorption wavelength λ = 461 nm was measured using a UV-Vis absorption spectrometer, and a linear fit was performed with iodine concentration C as the abscissa and absorbance A as the ordinate.
[0064] As shown in Figure 5, there is a good linear relationship between the concentration of iodine aqueous solution and absorbance, and the linear regression equation is: A = 0.70641C - 0.00424, R 2 = 0.99947.
[0065] The iodine adsorption performance of different organic small molecule single-crystal materials was tested using the following steps: Aqueous iodine adsorption experiments were conducted on individual single-crystal materials. 5 mg of the single-crystal material was added to 20 mL of iodine-saturated aqueous solution, and the mixture was allowed to stand for adsorption at room temperature and in the dark. Small amounts of the supernatant were collected at different adsorption times, and the changes in characteristic absorption peaks in the solution were measured using UV-Vis absorption spectroscopy. The iodine adsorption capacity of the single-crystal material was calculated based on the change in iodine concentration before and after adsorption.
[0066] Figure 6 The graph shows the UV-Vis absorption spectra of iodine aqueous solution during the adsorption process of single-crystal materials M1, M2, and M3. With increasing adsorption time, the absorbance of the iodine aqueous solution at the characteristic absorption wavelength gradually decreases, indicating that iodine in the solution is continuously adsorbed by the single-crystal materials. The absorption peak of system M3 decreases at a significantly faster rate than that of M1 and M2, indicating that protonation treatment can effectively improve the material's ability to capture iodine species in the aqueous phase.
[0067] To compare the adsorption rates of iodine by the three single-crystal materials M1, M2, and M3, adsorption capacity versus time curves were plotted. Figure 7 The figures show the iodine adsorption kinetics of three single-crystal materials. The results indicate that all three materials exhibit significant iodine adsorption capacity. With increasing adsorption time, the adsorption capacity of the materials gradually increases, eventually reaching adsorption equilibrium. Among them, the protonated single-crystal material M3 exhibits a faster adsorption rate and a higher iodine adsorption capacity within the same time frame.
[0068] To further compare the maximum iodine adsorption capacity of the three single-crystal materials M1-M3, capacity calculations were performed on the single-crystal materials after reaching adsorption equilibrium. The equilibrium iodine adsorption capacities of the three single-crystal materials are shown in Table 2. Table 2 shows that all three single-crystal materials exhibit high iodine adsorption performance, with the protonated single-crystal material M3 showing the highest equilibrium adsorption capacity. Compared to the other neutral single-crystal materials, M3 has a stronger iodine adsorption capacity.
[0069] Table 2. Equilibrium iodine adsorption capacity of three single-crystal materials
[0070] Further analysis was conducted on the crystal structure stability of M3, the single-crystal material with the highest iodine adsorption capacity, during the adsorption process. Powder X-ray diffraction (PXRD) tests were performed on M3 before and after iodine adsorption to obtain the PXRD spectra of M3 before and after iodine adsorption (e.g., ...). Figure 8 (As shown). From Figure 8 It can be concluded that M3 still maintains the main diffraction peak after iodine adsorption, indicating that the material has good structural stability during the aqueous iodine adsorption process.
[0071] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims, and the specification and drawings can be used to interpret the content of the claims.
Claims
1. A double-triangular-pore figure-eight shaped small-molecule single-crystal material, characterized in that, The single crystal material is prepared by a Schiff base condensation reaction of an aldehyde monomer represented by any one of the following formulas (I) or (II) and an amine monomer represented by any one of the following formulas (III), (IV) or (V). Among them, the single crystal material obtained by the aldehyde monomer shown in formula (I) or formula (II) and the amine monomer shown in formula (V) is prepared by Schiff base condensation reaction and protonation of nitrogen-containing sites by protonating reagent; 。 2. The single-crystal material according to claim 1, characterized in that, The single crystal material is prepared by Schiff base condensation reaction of aldehyde monomers shown in formula (I) or formula (II) and amine monomers shown in formula (III). Preferably, the single crystal material is prepared by Schiff base condensation reaction of an aldehyde monomer of formula (I) and an amine monomer of formula (III).
3. The single-crystal material according to claim 1, characterized in that, The single crystal material is prepared by Schiff base condensation reaction of aldehyde monomers of formula (I) or formula (II) and amine monomers of formula (IV). Preferably, the single crystal material is prepared by Schiff base condensation reaction of an aldehyde monomer of formula (II) and an amine monomer of formula (IV).
4. The single-crystal material according to claim 1, characterized in that, The single crystal material is prepared by Schiff base condensation reaction of aldehyde monomers shown in formula (I) or formula (II) and amine monomers shown in formula (V), followed by protonation of nitrogen-containing sites by a protonating agent. Preferably, the single crystal material is prepared by Schiff base condensation reaction of aldehyde monomers of formula (I) and amine monomers of formula (V), and then by protonation of nitrogen-containing sites with a protonating agent.
5. The single-crystal material according to claim 1, characterized in that, The protonating agent is trifluoroacetic acid.
6. The single-crystal material according to any one of claims 1-5, characterized in that, The aldehyde monomer of formula (I) is prepared by reacting salicylic acid with 1,4-dibromobutane; the aldehyde monomer of formula (II) is prepared by reacting salicylic acid with 1,6-dibromohexane.
7. A method for preparing the single-crystal material according to any one of claims 1-6, characterized in that, Includes the following steps: (1) The aldehyde monomer and amine monomer are dissolved in an organic solvent and subjected to Schiff base condensation reaction under the conditions of catalyst and regulator to obtain an organic host containing an imine bond; (2) The reaction system containing the organic host is subjected to static reaction and crystal culture to obtain single crystal material; or the nitrogen-containing sites in the organic host are protonated in the presence of a protonating agent and crystal culture is carried out to obtain single crystal material.
8. The preparation method according to claim 7, characterized in that, In the process of preparing single-crystal materials from aldehyde monomers represented by formula (I) or formula (II) and amine monomers represented by formula (III) or formula (IV), the catalyst is pure acetic acid and the regulator is aniline.
9. The preparation method according to claim 7, characterized in that, In the process of preparing single-crystal materials from aldehyde monomers of formula (I) or formula (II) and amine monomers of formula (V), the catalyst is trifluoroacetic acid and the regulator is trifluoroethylamine.
10. The use of the single crystal material according to any one of claims 1-6 or the single crystal material prepared by the preparation method according to any one of claims 7-9 in the preparation of iodine adsorbent materials.